PENGARUH BEBAN KERJA DAN PELATIHAN MELALUI MOTIVASI SEBAGAI VARIABEL MEDIASI TERHADAP KINERJA PERAWAT RUANG RAWAT INAP RSUD PURI HUSADA DI TEMBILAHAN - Sasmita, Jumiati (Jurnal Tepak Manajemen Bisnis, 2014)
The research was intended to find out the effect of job responsibilities and training or workshop toward performance and motivation variable as mediating.The data were collected by giving questionaires to 80 nurses by using Slovin that was determined by the cluster sampling method. The research used qualitative and quantitative. The population of the research was 100 nurses of the treatment rooms of Puri Husada RSUD in Tembilahan. There were 80 respondents by using cluster sampling method. model. Analysis model used by path analysis. The research proved that job responsibilities had a positive impact toward motivation but it was not a significant influence, Training or workshop gave a positive and significan impact towar d motivation, job r esponsibilities gave a positive and significant performance, training or workshop gave a positive and significant impact toward performance and motivation gave positive impact toward performance but it was not significant. Meanwhile, the results of the research could not prove that motivation gave mediation between job responsibility and and performance, the influences of training toward performance.Keywords : Job Responsibility , Motivation, T raining, performance.